Arthroscopic Debridement of Intrapelvic Abscess With Coexistent Septic Hip in an Adult Female: A Technical Note - Shahriar Seddigh, M.D; Alexandra Bishop, M.D; Ivan Wong, M.D., F.R.C.S. (C.) (Elsevier, 2020)
The aim of this study was to describe the technique for debridement of an intrapelvic abscess through an arthroscopic approach. We present a 24-year-old female with an obturator internus muscle abscess that extended across the obturator membrane and into the hip joint. Decompression of the intrapelvic abscess through hip arthroscopy was planned after close examination of preoperative images. Intrapelvic space was safely accessed by hip arthroscopy. The patient was asymptomatic and had normalized biomarkers at 6 months; however, the abscess recurred at 1 year postoperation. Details of the technique for intrapelvic access and anatomic structures at risk are described in this study.